A Decade of Biochemical and Structural Studies of the DNA Repair Machinery of Deinococcus radiodurans - Timmins, Joanna (2019)
The Deinococcus radiodurans bacterium is extremely resistant to ionising radiation and desiccation and can withstand a 200-fold higher radiation dose than most other bacteria with no loss of viability. The mechanisms behind this extreme resistance are not fully understood, but it is clear that several factors contribute to this phenotype. Efficient scavenging of reactive oxygen species and repair of damaged DNA are two of these. In this review, we summarise the results froma decade of structural and functional studies of the DNA repair machinery of Deinococcus radiodurans and discuss how these studies have contributed to an improved understanding of the molecular mechanisms underlying DNA repair and to the outstanding resistance of Deinococcus radiodurans to DNA damaging agents.